2022
DOI: 10.55463/issn.1674-2974.49.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cephalometric Measurements of On-Screen Images by CephX Software and Hard-Copy Printouts by Conventional Manual Tracing

Abstract: Newer diagnostic methods have become widespread in medicine nowadays as a result of extraordinary advancements in the field of electronics. On computers, various orthodontic programs are available as software. When it comes to orthodontics, diagnosis is critical, with the radiographic study being the most important phase. The goal of this research was to assess the level of liability of direct digital radiograph tracing using CephX and compare with hand tracing digital printouts and evaluate the two techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…These problems with lower incisor identification were also found in our study, yielding the high variability shown in the measurements presented in Figure 4C,D. Ribwar and Azeez compared the results of CephX and manual tracings [46]. The authors have shown that, except for several parameters, the results of the automated analysis showed high agreement with the manual method.…”
Section: Discussionsupporting
confidence: 77%
“…These problems with lower incisor identification were also found in our study, yielding the high variability shown in the measurements presented in Figure 4C,D. Ribwar and Azeez compared the results of CephX and manual tracings [46]. The authors have shown that, except for several parameters, the results of the automated analysis showed high agreement with the manual method.…”
Section: Discussionsupporting
confidence: 77%
“…All the studies showed some inaccuracies in the results of automated cephalometric analyses conducted with CephX. Despite these issues, the authors found the program useful [ 20 , 35 , 36 ]. The study by Meric and Naoumova [ 20 ] investigated the application of AI analysis based on lateral cephalograms of 40 patients preceding orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A notable advantage of CephX was the significant reduction in analysis time despite the need for manual correction. A study by Khalid and Azeez [ 36 ] analyzed results of cephalometric analysis based on 14 measurements on 25 lateral cephalograms, comparing an expert’s measurements with CephX results. A high level of agreement was demonstrated, except for measurements of two measurements.…”
Section: Discussionmentioning
confidence: 99%